A 0‐Hour/1‐Hour Protocol for Safe, Early Discharge of Chest Pain Patients. (26th July 2017) - Mokhtari, Arash; Lindahl, Bertil; Schiopu, Alexandru; Yndigegn, Troels; Khoshnood, Ardavan; Gilje, Patrik; Ekelund, Ulf
Abstract: Objectives: Guidelines recommend a 0‐hour/1‐hour high‐sensitivity cardiac troponin T (hs‐cTnT) diagnostic strategy in acute chest pain patients. There are, however, little data on the performance of this strategy when combined with clinical risk stratification. We aimed to evaluate the diagnostic accuracy of an accelerated diagnostic protocol (ADP) using the 0‐hour/1‐hour hs‐cTnT strategy together with an adapted Thrombolysis In Myocardial Infarction (TIMI) score and electrocardiogram (ECG) for ruling out major adverse cardiac events (MACE) within 30 days. Methods: This prospective observational study enrolled consecutive emergency department (ED) chest pain patients. TIMI score variables, ED physicians' assessments of the ECG, and 0‐ and 1‐hour hs‐cTnT were collected. Thirty‐day MACE was defined as acute myocardial infarction (AMI), unstable angina (UA), cardiogenic shock, ventricular arrhythmia, atrioventricular block, cardiac arrest, or death of cardiac or unknown cause. Results: A total of 1, 020 patients were included in the final analysis. The combination of an adapted TIMI score ≤1, a nonischemic ECG, and either a 0‐hour hs‐cTnT < 5 ng/L or a 0‐hour hs‐cTnT < 12 ng/L combined with a 1‐hour increase < 3 ng/L identified 432 (42.4%) patients as very low risk with a negative predictive value of 99.5% (95% confidence interval [CI] = 98.3%–99.9%) and a negative likelihood ratio of 0.04 (95% CI = 0.01–0.14) for 30‐day MACE. The ADP missed only two patients with UA and no patients with AMI or other forms of MACE. Conclusion: An ADP using the guideline recommended 0‐hour/1‐hour hs‐cTnT strategy rapidly identified patients with a very low risk of 30‐day MACE including UA where no further cardiac testing would be needed. This could potentially allow safe early discharge of about 40% of ED chest pain patients.